PHRASEOLOGICAL IMAGE AND MOTIVATIONAL MODEL (Scientific journal of the Fergana State University, 2025)
This article examines the components of a phraseological image and characterizes a two-component motivational model. An analysis of the facts on literal and metaphorical perceptions was carried out. Attention was drawn to the development of the connotative aspect of phraseological meaning, which manifests itself in certain structural and semantic models of phraseological units.